2017
DOI: 10.1016/j.molcel.2017.09.034
|View full text |Cite|
|
Sign up to set email alerts
|

CDK4 Phosphorylates AMPKα2 to Inhibit Its Activity and Repress Fatty Acid Oxidation

Abstract: The roles of CDK4 in the cell cycle have been extensively studied, but less is known about the mechanisms underlying the metabolic regulation by CDK4. Here, we report that CDK4 promotes anaerobic glycolysis and represses fatty acid oxidation in mouse embryonic fibroblasts (MEFs) by targeting the AMP-activated protein kinase (AMPK). We also show that fatty acid oxidation (FAO) is specifically induced by AMPK complexes containing the α2 subunit. Moreover, we report that CDK4 represses FAO through direct phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 70 publications
(99 reference statements)
2
49
0
1
Order By: Relevance
“…Altogether, the general function of CDK4 is to redirect energy availability to biosynthetic processes, rather than to energy-consuming processes like heat generation and dissipation, resulting for example in a decrease in BAT activation. This is consistent with the known role of CDK4 in controlling several biosynthetic pathways (Lagarrigue et al, 2016;Lopez-Mejia et al, 2017).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Altogether, the general function of CDK4 is to redirect energy availability to biosynthetic processes, rather than to energy-consuming processes like heat generation and dissipation, resulting for example in a decrease in BAT activation. This is consistent with the known role of CDK4 in controlling several biosynthetic pathways (Lagarrigue et al, 2016;Lopez-Mejia et al, 2017).…”
supporting
confidence: 90%
“…Growing evidence demonstrates that a regulatory crosstalk exists between metabolic pathways and regulators of cell cycle progression. Our laboratory and others have demonstrated that CDK4 is one of such "metabolic" cell cycle regulators (Blanchet et al, 2011;Denechaud et al, 2016;Lagarrigue et al, 2016;Lopez-Mejia et al, 2017). CDK4 participates in the G1/S transition phase of the cell cycle.…”
Section: Introductionmentioning
confidence: 96%
“…Oncogene Non-small cell lung cancer [7,8] , cervical cancer [7] , melanoma [7,9] , liposarcoma [10] and others Cell-cycle check-point regulation, metabolism (anaerobic glycolysis) [11] 11 TLK2 Amplificatio n oncogene Oncogene Breast cancer [12,13] , glioblastoma [14] Genomic instability [12] , src signalling pathway [14] 12 IL6 Amplificatio n oncogene Oncogene Liver cancer [15] , breast cancer [16] , head and neck squamous cell carcinoma [17] , prostate cancer [15,18] STAT3 activation, insulin-growth factor signaling, inflammation 13 HAS2 Amplificatio n oncogene…”
mentioning
confidence: 99%
“…In doing so, AMPK promotes bioenergetics processes such as glycolysis, autophagy, and FAO, while concomitantly inhibiting energetically costly anabolic processes such as FA synthesis [157] . Importantly, palbociclib was recently shown to induce activation of AMPK [159] and CDK4 has been shown to suppress FAO by directly antagonizing AMPKa2 [160] . Therefore, AMPK activation may be a valuable therapeutic target to antagonize mTOR-mediated lipid metabolic reprogramming.…”
Section: Targeting Lipid Metabolic Rewiring In Drug Resistant Cancer mentioning
confidence: 99%